(untitled) (Experimental biology, 2020)
This paper presents the results of complex studies of pasture lands of Central Kazakhstan. The research was carried out on the territory of Karaganda region in the South-Eastern part of the Central Kazakhstan melkosopochnik. The article gives detailed geobotanical descriptions of plant communities and resources of pasture lands on two model farms of LLP "Atamura-Tabys" and KH "Er-DOS". Systematic analysis of all plant communities in the study area showed that the largest number of species is concentrated in the families Poaceae; Asteraceae; Rosaceae; Lamiaceae and Scrophulariaceae. Quality assessment of the fodder value of plant communities LLP "Atamura-Tabys" showed that community reedgrass - grass- sagebrush steppes with participation of shrubs and forb-herd grass-fescue-quack-grass meadow steppes are characterized by average quality pasture with a yield of 19.2 с/ha and 29.6 с/ha. Good fodder significance is characterized by a community of mixed-gramineous and grass-herdsman meadows where species with high and good fodder dignity predominate, and yields of 30.4 c/ha. In the plant communities of Peasant Farm «Er-DOS», the average quality indicator of pasture lands is characterized by mixed herbs-feather grass-spirea steppes and peat-land meadow in river floodplains with the participation of mixed-gramineous communities, where yields on average are 14.1 and 17.2 c/ha. Communities on steppe halophytic meadows should be attributed to pastures with a low quality index of feed significance with a low yield of 7.3 c/ha. Key words: Pasture, animal breeding, Central Kazakhstan hill chain, Karaganda region, Republic of Kazakhstan, productivity, vegetation, resources.